2019
DOI: 10.56093/ijas.v89i10.94608
|View full text |Cite
|
Sign up to set email alerts
|

Productivity enhancement of Indian mustard (Brassica juncea) through innovative crop establishment technique

Abstract: A field experiment was carried-out for two consecutive years 2016-17 and 2017-18 during winter at ICARDirectorate of Rapeseed and Mustard Research, Bharatpur, Rajasthan to evaluate the performance of Indian mustard (Brassica juncea L.) under innovative transplanting technique of crop establishment. The experiment was laid out in randomized block design with two factors, i) planting geometries, i.e. 30 × 30 cm (T1), 45 × 30 cm (T2) and 60 × 30 cm (T3) and ii) transplanting dates, i.e. 13th October (D1), 22nd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…The enhanced plant height in mustard under 30 cm × 30 cm spacing over other plant geometry might be due to competition for light at closer spacing as compared to wider spacing under transplanting. Similar results were also reported by Kumar et al [5], Singh et al [6] and Singh et al [7]. The significantly higher plant height under transplanting of 25 days old seedlings may be owing to the fact that optimum age of seedlings performed active growth which might have contributed to more vigorous growth and development.…”
Section: Crop Growth Parametetssupporting
confidence: 86%
“…The enhanced plant height in mustard under 30 cm × 30 cm spacing over other plant geometry might be due to competition for light at closer spacing as compared to wider spacing under transplanting. Similar results were also reported by Kumar et al [5], Singh et al [6] and Singh et al [7]. The significantly higher plant height under transplanting of 25 days old seedlings may be owing to the fact that optimum age of seedlings performed active growth which might have contributed to more vigorous growth and development.…”
Section: Crop Growth Parametetssupporting
confidence: 86%
“…On the other hand, crop geometries of 45 cm × 30 cm and 45 cm × 45 cm having higher plant population/ unit area resulted in higher seed yield. Our results confirm the findings of and Singh et al (2006); Sahar et al (2012) and Singh et al (2019).…”
supporting
confidence: 93%
“…In the increased population in narrow crop geometry, plants probably tended to be taller for getting light, which may result in increased plant height. Pandey et al (2015) and Singh et al (2019) also reported higher plant height with narrow spacing under transplanted Indian mustard. Among the different spacing, 60 cm × 45 cm accumulated significantly more dry-matter than rest of spacings owing to better growth and development of the individual plants.…”
mentioning
confidence: 86%
“…The no significant result was observed Singh et al [16] also reported transplanting of mustard on 13th October was found highly superior with respect to growth, physiological parameters, yield and yield attributes compared to transplanting done on 22nd October and 01st November. interaction of date of sowing and variety grain yield Singh [17] also conducted [18,19].…”
Section: Yield (Q) In Hecmentioning
confidence: 99%